Hericium erinaceus, in combination with natural flavonoid/alkaloid and B3/B8 vitamins, can improve inflammatory burden in Inflammatory bowel diseases tissue: an ex vivo study - Gravina, Antonietta Gerarda; Pellegrino, Raffaele; Palladino, Giovanna; Coppola, Annachiara; Brandimarte, Giovanni; Tuccillo, Concetta; Ciardiello, Fortunato; Romano, Marco; Federico, Alessandro (Frontiers in Immunology, 2023)
Hericium erinaceus, berberine and quercetin are effective in experimental colitis. It is unknown whether they can ameliorate inflammatory bowel diseases in humans. This ex vivo study aimed to evaluate the anti-inflammatory potential of a nutraceutical compound of H. erinaceus, berberine, quercetin, biotin and niacin (HBQ-Complex®) in inflammatory bowel disease patients. Tissue specimens were obtained either from Normal-Appearing Mucosa (NAM) or from Inflamed Mucosa (IM) in 20 inflammatory bowel disease patients. mRNA and protein expression of COX-2, IL-10, and TNF-α were determined in NAM and IM biopsy samples (T0). IM samples were then incubated in HBQ-Complex®, and COX-2, IL-10 and TNF-α tissue levels were evaluated at 120 minutes (T1) and 180 minutes (T2). Incubation with HBQ-Complex® resulted in a progressive decrease in gene and protein COX-2 and TNF-α expression at T1/T2 in the IM. IL-10 showed an opposite trend, with a progressive increase of mRNA and protein expression over the same time window. HBQ-Complex® decreased proinflammatory cytokines expression at the mRNA and protein levels in IBD tissue. On the contrary, mRNA and protein expression of the anti-inflammatory cytokine IL-10, showed a progressive increase.